Mental Health Conditions Among University Students - Andi Tenri Faradiba; Bagas Rahmatullah (Education Policy and Development, 2023)
College students are one of the populations that are vulnerable to mental health disorders; various reasons can cause this. Sometimes there are triggers that cause students to feel that their mental health is not good, such as academic fatigue, academic stress, social support, and others. This study aims to find out how the mental health conditions at a university in Jakarta are described. The study involved 207 participants from 7 faculties using the Patient Health Questionnaire-9, Generalized Anxiety Disorder-7, and Deliberate Self Harm Inventory questionnaires. The analysis technique used was accidental sampling, and the data analysis technique used the Independent Sample T-test. The results showed that men have lower levels of anxiety and depression than women, while women tend to hurt themselves more than men. In conclusion, every faculty has students who experience anxiety disorders, depression, and self-harm behavior. As for this research, it can be used as additional data from previous research, especially at the University where this study was taken. The limitations of this research are in the aspects of the sampling method and the limitations of measuring instruments.